FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN PROVINSI-PROVINSI DI PULAU SULAWESI - Tabita Maharani Wijaya, (2022)
This research aims the effect of labor absorption, human development index, and Income per capita on the poverty level of the provinces on the island of Sulawesi. The sampling technique in this research used a saturated sampling technique in 6 provinces during 2014-2019, so that a total sample of 36 data was obtained from the Central Bureau of Statistics (BPS). This research uses panel data analysis by combining time-series and cross-section data. The results of the partial study show that employment does not have a significant effect, the human development index has a significant negative effect, and income per capita has a positive effect on the poverty level.